Semiotic Analysis in Barbie Film by Charles Sanders Peirce's Theory - Astari, Arini Widi; Alamsyah, Alamsyah (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
This research discussed the meaning of the signs in the Barbie (2023) film. This research aimed to find the signs contained in the film based on the types of signs in Charles Sanders Peirce's semiotic and to interpret the meaning of these signs based on the semiosis process which involved the relationship between representamen, object, and interpretant. In this research, researchers used qualitative methods and data was collected by marking and sorting with a semiotic approach. The researcher found 4 types of signs: icon show that every woman has the same opportunities and rights as other women and has equal gender roles as men in society, qualisign show the feminine side of women and the sexual violence that women often experience, symbol shows allusions to sexism and patriarchal culture, and index shows self-discovery. Based on 4 types of signs that have been analyzed through a semiosis process involving representamen, object, and interpretant, the researcher found the meaning of this film was about the position of women in society, the importance of gender equality without gender stereotypes, women also had the same rights in a career regardless of their physical appearance and skin color, women had ambition and dreams and be able to play an active role in society as well as the meaning about the importance of being yourself.